One Direction The Official Annual 2015 (London Harper Collins Publishers, 2014)
The world's biggest band, One Direction, are back to share their backstage secrets and stories from the past year with their fans in the latest instalment of their must have annual. Packed full of exclusive interviews and never-before-seen photos, , discover everything you've ever wanted to know about Harry, Niall, Louis, Liam and Zayn, from their passions to influences and all the backstage gossip. Packed full of juicy info, this is the ultimate stocking staple for any One direction fan
Famous People
1 2 14
Keywords: Great Britain; One Direction -- Biography; One Direction (Musical group) -- Juvenile literature; One Direction (Musical group); Rock musicians -- Great Britain -- Biography -- Juvenile literature; Rock musicians